Caste and Islamic revivalist movements: a case study of Eastern Muslims in Sri Lanka - Aboobacker, Rameez (Penerbit Universiti Kebangsaan Malaysia, 2018)
Caste exists in all South Asian societies. Although the caste has become contentious among Sinhalese and Tamils in Sri Lanka, it suffered a fatal blow among the Tamils during the civil war. However, it has re-emerged once again during the post-war context. In contrast, the caste among Muslims in Sri Lanka gained no significance, since Islam has not subscribed to discrimination and inequality in the form of caste. Nevertheless, one may come across endogamous groups analogous to caste and such groups are subjected to certain discrimination among Muslims. As such, this study explores whether caste still exists among the Eastern Muslims of Sri Lanka and examines the role of Islamic revivalist movements in the caste dynamics. This study employed qualitative method for data collection such as observation, in-depth interviews and focus group discussions. It was found that various groups occupying a higher or lower strata of Muslim society in the Eastern Sri Lanka existed in the past, thanks to the influence of non-Muslim neighboring communities such as Tamils, as they live side by side in the Eastern Sri Lanka. However, such caste divisions do not exist anymore, given the Islamic revivalism that swept through South Asia including Sri Lanka in 1970s. Moreover, the study has also found that the advancement of education, westernization and globalization contributed significantly to erosion of caste discrimination among the Muslims in Eastern Sri Lanka.